About the publication of "the Russian-Lithuanian calendar" for 1873-1876 - Merkys, Vytautas (Knygotyra, 1988)
Until now, it was incorrectly stated that the Calendar was published periodically for 1873-1876 (compiled by I. Kretchinskij). As far as we know, not a single copy of this Calendar has been preserved (a slight mention in a Milovidov booklet from 1908 remains the basis of this article). Supplementary data were found in archives (the records of the Educational Guardian of the Vilnius district and others). It was proven that the Calendar was prepared for print in 1873 (and likely published), but on the other hand, its further publication was discontinued.